Pharmacy Staff's Recommendations for Self-Medication Requests on Non-Infectious Productive Cough: A Study in Padang City, Indonesia - Nasif, Hansen; Andrelva, Cynthia Bella; Sari, Yelly Oktavia (JSFK (Jurnal Sains Farmasi & Klinis), 2023)
Cough is a physiological reflex to liberate the airway from mucus or foreign objects. Many cough medicines in pharmacies require special expertise to select the proper medication according to the patient's condition. This research aims to evaluation recommendations of drugs for non-productive cough for self-medication from pharmacy staff in Kuranji subdistrict, Padang City.Â  A cross-sectional study with total sampling techniques is used for collecting data. This research uses a structured interview technique with the main question, what medicine would pharmacy staff recommend if an adult patient comes with a productive cough without any symptoms of infection? There are 30 pharmacies in Kuranji subdistrict, but data that meets the inclusion criteria is only from 25 pharmacies because five pharmacies are not willing to be research sites. Those who were willing to take part in this research were 16 pharmacists and nine non-pharmacist staff. Only 37.5% (6 of 16) of correct drug recommendations were given by pharmacists, and 33.3% (3 of 9) of proper drug recommendations were provided by non-pharmacist staff. There are still many things that could be improved in drug recommendations for this case, with a total average of correct administration of only 36%. The proper drug choices were Bromhexin and Acetylcysteine, while other drugs that were incorrectly chosen were drugs that should have been given with a doctor's prescription, branded drugs with more than one active ingredient , herbs or not the drug of choice for now.There are still many mistakes in the medicine choice, with an average total of only 36% accurate recommendations.